(untitled) (Journal of Mechanical Engineering, 2015)
Uniaxial tensile test was carried out at different loading direction (0o, 90o and 45o) on rolled aluminiumsheets. The anisotropic coefficient was analyzed to reveal formability characteristics. The shear strain that wasimposed during the ASR was extensive and the shear marks was inclined more or less linearly without beingzigzag or spiral lines. The ASRC improved the normal anisotropy coefficient compared to CR specimens. Thehighest normal anisotropy and the lowest planar anisotropy were observed by ASRC samples. Therefore, it wasfound that, asymmetric rolling especially ASRC can be used to improve the formability of aluminium thick sheets.